Quality by Design: A Strategic Approach to Pharmaceutical Development - Sharma, Mahavir M.; Brahmbhatt, Harshkumar; Shah, Priyanka; Vaghela, Ujjval P. (International Journal of Pharmaceutical Investigation, 2025)
This review delineates the primary objectives of Quality by Design (QbD) and provides an in-depth exposition of its foundational concepts. The core components of QbD include: (1) the establishment of a comprehensive control strategy that defines quality requirements for drug substances, excipients, and final pharmaceutical products, while incorporating controls at each stage of the manufacturing process; (2) product design and understanding, encompassing the identification and characterization of Critical Material Attributes (CMAs); (3) process design and understanding, which involves the identification of Critical Process Parameters (CPPs) and their interactions with CMAs and Critical Quality Attributes (CQAs); (4) the formulation of a Quality Target Product Profile (QTPP), outlining the desired CQAs of the final drug product; and (5) the evaluation of process capability and the implementation of continuous improvement strategies. The practical application of QbD is facilitated by a range of scientific methodologies, including prior knowledge, risk assessments, mechanistic modeling, Design of Experiments (DoE), data analytics, and Process Analytical Technology (PAT). As the pharmaceutical industry increasingly adopts QbD principles, the standardization of terminology and a unified conceptual framework are critical. Such alignment will enhance communication and collaboration among stakeholders, thereby supporting risk-based drug development and regulatory evaluation processes.
Keywords: Process Analytical Technology; Critical Quality Attributes; QBD